Effect of Dementia Training on Knowledge and Attitude Among Long-Term Care Staff in Yogyakarta, Indonesia - Mulyani, Sri; David Saifullah, Azam (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The number of patients with dementia has increased globally. Caring for these patients is very challenging and demanding. There are many patients with dementia in long-term care facilities in Yogyakarta, Indonesia. However, most staff members do not have proper training regarding how to care for patients with dementia. AIM: This research aimed to investigate the effect of dementia care skills training on knowledge and attitudes about dementia among long-term care staff in Yogyakarta, Indonesia. METHODS: A pre-experimental study was conducted using a one-group pre-test and post-test method. There were 30 staff members in a long-term care facility in Yogyakarta, Indonesia, who participated in this study in July 2019. Training given was the Dementia Care Skills 18 h version for care workers provided by Alzheimer’s Indonesia by two certified trainers. Outcomes measured were knowledge and attitudes of the participants, which were measured using the Dementia Knowledge Assessment Scale and Dementia Attitude Scale. Data were analyzed using paired and independent t-tests as well as Pearson correlation tests. RESULTS: The results showed that staff knowledge of dementia (t = 4.78, p = 0.000) and attitudes toward persons with dementia (t = 3.27, p = 0.003) were improved significantly after the dementia training provided by the Alzheimer’s Indonesia trainers. CONCLUSIONS: Training in dementia care can improve knowledge and attitude of long-term care staff. This study recommends that dementia care skills training be provided for staff and nurses in long-term care to improve their knowledge and attitudes regarding patients with dementia and their care.